Assessment of serum levels of anti‑cyclic citrullinated peptide antibodies in patients with psoriatic arthritis: A cross‑sectional study in a Brazilian cohort. Issue 5 (10th July 2020) - GRUBER, CRISTIANE; SKARE, THELMA; CAMPOS, ANA PAULA B.; SIMIONI, JULIANA; MAESTRI, VINICIUS; NISIHARA, RENATO
No abstract available